Calculation and Measurement of Dielectric Parameters of Ceramic and Ferroelectric Materials in the Microwave Range - V. S. Severikov; Kong Che Fam; V. I. Melnik (Известия высших учебных заведений России: Радиоэлектроника, 2023)
Introduction. Determination of the electrophysical parameters of linear and nonlinear dielectric materials for use in microwave technology represents an important direction. Linear dielectrics are used as a basis for the substrates of microwave circuits, as well as volumetric elements for the construction of frequency selective or resonant structures that operate across a wide temperature range. Therefore, the issue of stabilizing the electrical parameters of such structures from temperature influences appears relevant. A possible solution lies in the use of a multilayer combination of dielectrics, both with linear and nonlinear properties. Due to their nonlinear properties, ferroelectrics find application in functional units with an electrical rearrangement of frequency and phase characteristics. Therefore, it is important to determine not only the relative permittivity of the material, but also the control coefficient in the RF– microwave wavelength ranges.Aim. Construction of computational mathematical models for layered bulk and film structures to determine the relative permittivity of linear and nonlinear dielectrics in the ultrahigh frequency range.Materials and methods. The construction of computational mathematical models for the analysis of complex layered structures was carried out on the basis of Maxwell’s equations and the Galerkin method using boundary conditions for electromagnetic field components.Results. An electrodynamic analysis of a two-layer volumetric disk resonator was performed, and numerical results of calculating the resonant frequency were obtained. A numerical analysis of a multielectrode half-wave resonator with a ferroelectric film (FEF) was carried out.Conclusion. The mathematical models created and the experiment performed made it possible to numerically evaluate the properties of linear and nonlinear dielectric bulk and film materials in the microwave range.